Possible improvement of acoustical climate. Part I: Measurements and theoretical description - WALERIAN, Elżbieta; JANCZUR, Ryszard; CZECHOWICZ, Mieczysław; SMYRNOVA, Yulija (Archives of Acoustics, 2010)
In the paper, the simulation PROP5 program is used to predict the sound level in proximity of a road with defined surroundings. The simulation involves road geometry (number of lanes and their positions) and traffic structure (vehicle flow rates and their average speeds), with equivalent omnidirectional point sources representing vehicles. In Part I of the paper, the agreement between measurement and simulation results is tested to verify the accuracy degree of the applied models of a road, as a noise source and propagation throughout surrounding space. In Part II, using the pre-tested simulation program, the possibility of acoustic climate improvement has been analyzed.